A Re-Entry Program for Peacekeeping Soldiers: Promoting Personal and Career Transition - Westwood, Marvin J.; Black, Timothy G.; McLean, Holly B. (Canadian Journal of Counselling and Psychotherapy, 2007)
A re-entry program for peacekeeping soldiers is described. This program was developed to assist with military personnel's transition back into Canadian society by aiding with their personal and career re-adjustment. Group-based life review and therapeutic enactment counselling interventions are used to identify critical incidents and facilitate the resolution of stress-related reactions soldiers have experienced after a peacekeeping mission. The principle guiding the development of this program is the belief that free from the distraction of these stress reactions and accompanying personal difficulties, soldiers are better able to concentrate on career-building activities. An overview of the program is presented along with a case study to exemplify how the program is applied in practice.